Sudden fetal death with placental mesenchymal dysplasia complicated by placenta previa. Issue 11 (17th August 2021) - Tanimura, Kenji; Shi, Yutoku; Imafuku, Hitomi; Nakanishi, Takaaki; Kanzawa, Maki; Terai, Yoshito
Abstract: Placental mesenchymal dysplasia (PMD) is a rare placental abnormality that is closely related to severe pregnancy complications. A 27‐year‐old woman with fetal growth restriction and placenta previa was referred to a university hospital at 22 gestational weeks (GW). She was suspected of having a twin pregnancy with a complete or partial hydatidiform mole and coexisting normal live fetus, because two separate placentas, an enlarged one with multiple cystic lesions and a normal one, were shown on ultrasound examinations. At 27 GW, she experienced a sudden intrauterine fetal death (IUFD) after bleeding due to placenta previa, despite confirmation of fetal well‐being at 2 h before bleeding. After delivery, histopathological examination confirmed the diagnosis of PMD. This is the first documented case of a woman with PMD and placenta previa who had a sudden IUFD after bleeding. Patients with both PMD and placenta previa should be considered at extremely high risk for IUFD.